Positron-impact ionization studied by means of Recoil-Ion momentum distributions - Barrachina Tejada, Raul Oscar (2012)
We investigate ionization processes induced by positron impact by studying the momentum distributions of the receding ion by means of Classical Trajectory Monte Carlo techniques. We compare the recoil momentum distributions with those of the electron and positron.